2016
DOI: 10.3233/jad-150707
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia

Abstract: Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
2
20
1
1
Order By: Relevance
“…In contrast, we found the preservation of proteins necessary for vesicular exocytosis, such as SNAP25, STX1A, and SV2B . Despite the interaction of α‐synuclein with synaptic proteins, previous studies have not consistently demonstrated significantly lower levels of presynaptic markers in DLB …”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In contrast, we found the preservation of proteins necessary for vesicular exocytosis, such as SNAP25, STX1A, and SV2B . Despite the interaction of α‐synuclein with synaptic proteins, previous studies have not consistently demonstrated significantly lower levels of presynaptic markers in DLB …”
Section: Discussioncontrasting
confidence: 73%
“…41 Despite the interaction of a-synuclein with synaptic proteins, previous studies have not consistently demonstrated significantly lower levels of presynaptic markers in DLB. 42 The role of glia in DLB has been a matter of controversy and debate, with conflicting reports in the literature. Microglial activation is induced by aggregated asynuclein in vitro, 43 although postmortem studies have reported inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, pSer396 tau changes did not reach statistical significance due to variability (see Additional file 4: Figure S4a), and higher N ’s may be needed to have sufficient power to study potential correlations between different pCRMP2 species and tau phosphorylation, especially since certain pCRMP2, e.g., 3 F4 epitopes, are known to be associated with neurofibrillary tangles [55]. With regards to α-synuclein, we found no difference in levels of monomeric species in agreement with previous studies [48, 49], and no correlations between α-synuclein and pCRMP2 (Additional file 5: Figure S5). In contrast, α-synuclein phosphorylated at Ser129 in insoluble fractions was significantly elevated in DLB, whilst PDD showed intermediate levels, and may be more specific to [56], and pathogenic in [57], LBD, similar with previous finding [58] (Additional file 6: Figure S6).…”
Section: Discussionsupporting
confidence: 89%
“…2a). Interestingly, PDD and DLB are known to have similar α-synuclein loads as well as Lewy body burden [19, 48, 49] (also see Additional file 5: Figure S5), suggesting that at least some of the identified neurochemical differences between PDD and DLB could be driven by the different Aβ burden in the subtypes. This postulate is recently supported by the finding that low cerebrospinal fluid Aβ42 values predicted a more rapid cognitive decline in DLB [50].…”
Section: Discussionmentioning
confidence: 99%
“…Szignifikáns csökkenés mutatkozik a szinaptikus vesiculák dokkolásában részt vevő synaptotagmin, synapsin, synaptophysin, VAMP2 és SNAP25 fehérjék szintjében [32]. Következésképpen a preszinaptikus neuronokból nem tudnak neurotranszmitterek felszabadulni, így a posztszinaptikus sejtek elvesztik "input"-jaikat, ami a központi idegrendszer kiterjedt funkciózavarához vezet, ezt a posztszinaptikus PSD95, valamint a neurogranin fehérje csökkent szintje is alátámasztani látszik.…”
Section: Változások a Neurotranszmisszióbanunclassified